2015
DOI: 10.19182/bft2016.327.a31293
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Forest Cover and Carbon Stock Change in the Democratic Republic of Congo: Case of Wood-Fuel Supply Basin for Kinshasa

Abstract: Afin de contribuer à la mise au point de mé- thodes de gestion durable des écosystèmes forestiers en Afrique centrale, la question de recherche suivante a été posée : l’analyse de l’évolution de la couverture végétale per- met-elle de comprendre et de documenter l’organisation spatiale et les mécanismes de la dégradation des forêts tropicales ? Pour cela, en République démocratique du Congo, le projet Makala a cartographié les arbres et les ressources forestières du bas- sin d’approvisionnement en bois-énergie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
3
1
4
Order By: Relevance
“…These differences were attributed not only to the plant species composition of fallow, in contrast to the methodological difference, especially the definition of young and old fallow. In fact, in our study, the age of young fallows is between 1 and 2 years whereas it is 4 to 8 years in the studies of Anobla and N'Dja [46], 5 years in those of Kaïré [51], Da Costa [41] and Palm et al [48], less than 10 years in those of Mass [52]. Similarly, the age of old fallows is 20 years in our work and those of Kaïré [51] versus 10 years in the work of Mass [52] and 25 years in those of Palm et al [48].…”
Section: Carbon Stockcontrasting
confidence: 56%
See 1 more Smart Citation
“…These differences were attributed not only to the plant species composition of fallow, in contrast to the methodological difference, especially the definition of young and old fallow. In fact, in our study, the age of young fallows is between 1 and 2 years whereas it is 4 to 8 years in the studies of Anobla and N'Dja [46], 5 years in those of Kaïré [51], Da Costa [41] and Palm et al [48], less than 10 years in those of Mass [52]. Similarly, the age of old fallows is 20 years in our work and those of Kaïré [51] versus 10 years in the work of Mass [52] and 25 years in those of Palm et al [48].…”
Section: Carbon Stockcontrasting
confidence: 56%
“…Indeed, in Saré Yorobana, in southwestern Senegal, Kaïré [51] found in the fallows of 5, 10, 15 and 20 years, an increase in the carbon stored in the biomass of 5, 11, 15 and 18 tC.ha -1 , respectively. The results obtained by Mass [52] in the same site as Kaïré [51] showed that fallows less than 10 years accumulated on average a carbon stock (soil + plant) of 17.5 tC.ha -1 , whereas Fallows older than 10 years averaged 22.5 tC.ha -1…”
Section: Carbon Stockmentioning
confidence: 99%
“…Kashaigili and Majaliwa [ 16 ] also realized a reduction in carbon stock from the year 1980 to 2010 in two forests of Tanzania due to forest cover change. Similarly, Gond et al [ 74 ] also reported a 30% loss in carbon stock from 1984 to 2012 in wood-fuel supply basin of Kinshasa. Furthermore, Gaston et al [ 44 ] showcased a loss in above ground carbon stock by 6.6 Pg due to forest degradation in tropical Africa between 1980 and 1990.…”
Section: Discussionmentioning
confidence: 88%
“…The PB area is one of the main supply zones of the capital city Kinshasa with over 10 million inhabitants, supplying an estimated 40% of its total demand (Projet Makala, 2011). The area has known a significant reduction of forest stock and degradation due to shifting cultivation and charcoal production, with an estimated decrease of carbon stock by 75% over 20 years' time (Gond et al, 2016).…”
Section: Efficiency Of Wood-to-charcoal Conversion Near Yangambi Man mentioning
confidence: 99%